2016
DOI: 10.1080/13803395.2016.1250869
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in HIV effects on visual memory among substance-dependent individuals

Abstract: HIV’s effects on episodic memory have not been compared systematically between male and female substance-dependent individuals. We administered the Brief Visuospatial Memory Test–Revised (BVMT–R) to 280 substance-dependent HIV+ and HIV− men and women. Groups were comparable on demographic, substance use, and comorbid characteristics. There were no significant main effects of sex or HIV serostatus on BVMT–R performance, but HIV+ women performed significantly more poorly on delayed recall. This effect was most p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 73 publications
2
19
1
Order By: Relevance
“…Our finding that both HIV-infected men and women showed poorer delayed recall compared with HIV-uninfected groups replicates and extends the previous report by Morales et al (2012) by demonstrating that spatial episodic memory impairment among HIV-infected individuals is not sex specific and is detectable among substance users. Additionally, these results are generally consistent with previous reports of impairment in verbal and visual episodic memory among HIV-infected individuals (Maki et al 2015; Keutmann et al 2016; Heaton et al 2011), indicating that episodic memory impairment associated with HIV disease is not modality specific.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our finding that both HIV-infected men and women showed poorer delayed recall compared with HIV-uninfected groups replicates and extends the previous report by Morales et al (2012) by demonstrating that spatial episodic memory impairment among HIV-infected individuals is not sex specific and is detectable among substance users. Additionally, these results are generally consistent with previous reports of impairment in verbal and visual episodic memory among HIV-infected individuals (Maki et al 2015; Keutmann et al 2016; Heaton et al 2011), indicating that episodic memory impairment associated with HIV disease is not modality specific.…”
Section: Discussionsupporting
confidence: 91%
“…These included measures of spatial working memory (n-back) (Hinkin et al 2002), strategic memory (HVLT) (Benedict et al 1998), index of semantic clustering (Woods et al 2005, Meyer et al 2014), and visuospatial episodic memory (BVMT-R Delayed Recall) (Benedict et al 1996; Keutmann et al 2016). We selected these measures based on known sensitivity to HIV effects and as validated measures of episodic memory or spatial processing.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite our sample size of 73, we may have been underpowered to detect small effects given the 2×2 design. In addition, prior studies have found that women may be more vulnerable than men to HIV-associated neurocognitive impairments (Martin et al, 2011; Martin et al, 2016), especially in the context of co-occurring drug abuse (Keutmann et al, 2016). While we did not detect an effect of sex, larger sample sizes are needed to sufficiently explore the potential moderating effects of sex and other biological factors.…”
Section: Discussionmentioning
confidence: 99%